Terrestrial Complex for Receiving Information from Small Spacecrafts - Makarov, S. B.; Zavjalov, S. V.; Volvenko, S. V.; Lavrenyuk, I.; Vinnichenko, M. Ya.; Aharonyan, A. K.; Avetisyan, V. H.
The work is devoted to the development of a terrestrial complex for receive and process information from small spacescrafts. The main requirement for these stations is their simplicity and maximum availability both in terms of cost and operating capabilities. Such stations provide a two-way exchange of information with spacecrafts in the frequency range 435-438 MHz, receive and process data transmitted in the VHF band by amateur and student satellites, and receive communications from the international space station crew and radio amateurs on Earth.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture